2013
DOI: 10.1007/s00436-013-3605-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy identifies a new species of Phyllodistomum (Digenea: Gorgoderidae) from the twospot livebearer, Heterandria bimaculata (Teleostei: Poeciliidae), in Central Veracruz, Mexico

Abstract: Phyllodistomum inecoli n. sp. is described from the twospot livebearer, Heterandria bimaculata (Teleostei: Poeciliidae), collected in the Río La Antigua basin, Veracruz, Mexico. The new species is described and characterised by using a combination of morphology, scanning electron microscopy, and sequences of nuclear and mitochondrial genes. Diagnostic characters of the new species of Phyllodistomum include a genital pore opening at the level of the caecal bifurcation; oval vitellarium, situated just posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Recent molecular phylogenetic studies on members of the Gorgoderidae showed that Phyllodistomum is paraphyletic [16,17], as also confirmed in the present study. The broad and foliate hindbody of Phyllodistomum is a key morphological character separating this genus from Gorgoderina and Gorgodera, and furthermore Gorgodera has more testes than Phyllodistomum and Gorgoderina [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent molecular phylogenetic studies on members of the Gorgoderidae showed that Phyllodistomum is paraphyletic [16,17], as also confirmed in the present study. The broad and foliate hindbody of Phyllodistomum is a key morphological character separating this genus from Gorgoderina and Gorgodera, and furthermore Gorgodera has more testes than Phyllodistomum and Gorgoderina [10].…”
Section: Discussionsupporting
confidence: 91%
“…Two adult flukes of the new species were individually subjected to DNA Phyllodistomum brevicecum Steen, 1938, a bladder fluke of North American freshwater fish [16], showed the relatively high BLAST scores of 97% identity to 28S rDNA and 87% identity to cox1.…”
Section: Molecular Comparison With Other Speciesmentioning
confidence: 99%
“…of Ginetzinskaya, 1959) P. amnicum Pond near Rybinsk Water Reservoir on River Volga, RussiaKX957730KY307874 Phyllodistomum sp. b (identified as P. pseudofolium ) Perca fluviatilis Rybinsk Water Reservoir on River Volga, RussiaKY307869KY307886 Phyllodistomum macrocotyle a Dreissena polymorpha Lake Vilkokšnis, LithuaniaKJ729518, KJ729522, KJ729526 [27]KJ740518, KJ740519 [27] P. macrocotyle a D. polymorpha Elektrėnai Water Reservoir, LithuaniaKJ729525 [27]KJ740516 [27] P. macrocotyle a D. polymorpha Lake Wigry, PolandKJ729520 [27]KJ740520, KJ740521, KJ740522 [27] P. macrocotyle a D. polymorpha River Shumorovka, RussiaKJ729521, KJ729524 [27]KJ740523 [27] P. macrocotyle a ( = P. folium sensu Sinitsin, 1905) D. polymorpha Lake Lepelskoe, BelarusAY288828 [63]AY288831 [63] P. macrocotyle a ( = P. folium sensu Sinitsin, 1905) D. polymorpha Lake Lukomskoe, BelarusAF533015 [63]AF533015 [63] P. magnificum Tandanus tandanus Moggill Creek, Queensland, AustraliaKF013186, KF013189 [53]KF013153, KF013156 [53] P. inecoli Heterandria bimaculata Agua Bendita, Xico, Veracruz, MexicoKC760199 [8] P. inecoli Profundulus sp.Rio Templo, San Juan del Rio, MexicoKM659389 [10] P. spinopapillatum Profundulus balsanus Rio PuebloViejo, San Gabriel Mixtepec and Rio Santa Cruz, Santiago Jamiltepec, MexicoKM659382, KM659388 [10] P. centropomi Centropomus parallelus Tlacotalpan, Veracruz, MexicoKM659384 [10] P. kanae Hynobius retardatus Pippu, Hokkaido, JapanAB979868 [7] P. brevicecum Umbra limi Brokenhead, Manitoba, Ca...…”
Section: Methodsmentioning
confidence: 99%
“…While morphology may not be enough to establish robust species delimitation criteria, scanning electron microscopy (SEM) studies have revealed distinct patterns of the distribution of papillae on the body surfaces of species of the family Gorgoderidae [34–37], including species of Phyllodistomum [8–10, 38–43]. These studies have suggested that the arrangements of these tegumental papillae on adult gorgoderid species represent useful taxonomic characters.…”
Section: Introductionmentioning
confidence: 99%
“…This framework emphasises an integrative approach to taxonomy (Dayrat, 2005;Will et al, 2005) rather than one based on singular criteria, and has already been successfully applied to recognise many trematode species (e.g. Georgieva et al, 2013, Razo-Mendivil et al, 2013Georgieva et al, 2014 in association with Faltýnková et al, 2015;Blasco-Costa et al, 2014 in association with Faltýnková et al, 2014;Herrmann et al, 2014;Diaz et al, 2015). This approach is not completely new to parasite taxonomists, since ecological data (e.g.…”
Section: Species Concepts Applied To Trematodes In the Molecular Agementioning
confidence: 99%